The correlation between personal creativity and the emotional sphere during adulthood in conditions of the COVID-19 pandemic - Anna Yu. Shmiganovskaya (Saratov State University, 2023)
The relevance: The COVID-19 pandemic became an unprecedentedly serious test for many Russian people. This negatively affected their psycho-emotional state. Therefore, the search for protective factors that can minimize the negative effects of the pandemic has become an urgent psychological task. The objective is to study the correlation between the individual's creativity and the indicators of the emotional sphere of an adult in conditions of the COVID-19 pandemic. The study hypothesizes that personality creativity is connected with the manifestation degree of the stress experienced, of depression and anxiety manifestation in mentally healthy adult respondents in conditions of the COVID-19 pandemic. Participants: 200 respondents aged 19 to 55 (M = 35.83, SD = ±13.16), 55% are men, 45% are women. The study methods (tools). To study the intensity and specific features of the respondents' experiences during the COVID-19 pandemic, the questionnaire "Psychological Experiences in a Pandemic" (by O. V. Rychkova, A. Y. Shmiganovskaya) was used; to determine the level characteristics of anxiety, depression and stress, the "DASS-21" questionnaire (by S. Lovibond and P. Lovibond) was used; to measure the creativity level of the respondents' personality, the "Creativity Questionnaire" (by D. Johnson) was used. The results. The study allowed us to discover, statistically prove and describe the correlation between the personality creativity and emotional maladjustment indicators (expressed as the symptoms of depression, anxiety, and stress experienced) which were observed in the conditions of the negative impact of the COVID-19 pandemic on mentally healthy individuals: adults with a higher level of personality creativity are less susceptible to the negative psychological impact of such a crisis situation as a pandemic. The conclusions. The results obtained made it possible to substantiate the correlation between the personality creativity and the adults' emotional sphere indicators. More creative people have lower levels of worries, stress, anxiety and depression in the context of the COVID-19 pandemic. It proves the necessity and relevance to search for and test psychological practices that contribute to the development of the personal creativity during a crisis and periods of high psycho-emotional load. In particular, it is recommended to conduct art therapy in a distance format when working with adults.